Genetic similarity between donor and recurrent parents can reduce the number of backcross generation in marker-assisted backcross - de Souza, Elton Otacílio; Môro, Gustavo Vitti [UNESP]; Rodrigues, Gabriel Belfort; Schuster, Ivan (Springer Nature, 2022)
The marker assisted backcross (MABC) method is the most used to obtain transgenic hybrid and transgenic inbred lines in maize with few backcrosses (BC) generations. It is possible that the use of donor parents with greater genetic similarity with recurrent parents can further reduce the number of BC generation to recover recurrent parent genome. The objective of this study was to verify the influence of genetic distance between parents and the percentage of recurrent parent genome recovery, as well as the similarity of BC plants and recurrent parent. Nine maize BC populations were evaluated, with genetic distances between donors and recurrent parents ranging from 0.238 to 0.499. In the backcross generations, molecular markers were used to identify the plants with the highest percentage of recurrent genome recovery and with greater similarity to the recurrent parent. There was no difference in the recurrent genome recovery among populations after three BC generations. In the first two BC generation the similarity between BC plants and recurrent parents was positively correlated with the similarity between donor and the populations recurrent parent. BC populations with higher similarity among parents could be finished with two BC generations, and BC populations with lower similarity could just be finished after three generation of MABC. The use of donor parents with higher similarity with recurrent parent can reduce one BC generation in MABC approach.
Keywords: Genetic diversity; Marker-assisted backcross; Single nucleotide polymorphism markers; Trait introgression; Zea mays L